K*(892)$^+$ production in proton-proton collisions at $E_{beam}=$ 3.5 GeV - HADES collaboration (98 authors) (2015)
We present results on the K*(892)+ production in proton-proton collisions at a beam energy of E=3.5 GeV, which is hitherto the lowest energy at which this mesonic resonance has been observed in nucleon-nucleon reactions. The data are interpreted within a two-channel model that includes the three-body production of K*(892)+ associated with the Λ or Σ hyperon. The relative contributions of both channels are estimated. Besides the total cross section σ(p+p→K*(892)++X)=9.5±0.9−0.9+1.1±0.7μb, which adds a new data point to the excitation function of the K*(892)+ production in the region of low excess energy, transverse momenta and angular spectra are extracted and compared with the predictions of the two-channel model. The spin characteristics of K*(892)+ are discussed as well in terms of the spin-alignment.